The role of media in advocating learning disability programme in Malaysia : pre-and in-service teacher perception - Saad, Supiah; Nayan, Nordina; Ibrahim, Haniz (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2013)
Are mainstream in Malaysia knowledgeable about types of student with special needs, are there enough support services as well as facilities provided for these students’ education? Ministry of Education Malaysia is implementing inclusive education (IE) since 1960s and currently 6% of students with special educational needs are in mainstream settings. Based on international best practices and current national policy theMOE is committed to moving more students with special needs towards Inclusive Education. The transition projection of Inclusive Education enrolment in 2015 is 50% and it is targeted to achieve 75% in 2020 when Malaysia become develop country. The finding of previous researchs show that mainstream teachers’ attitude toward SEN students were negative due to lack of information and awareness. This study investigated the roles of media in advocating special education programmes in Malaysia. The sample consisted of 296 students of bachelor degrees in two public universities, 39 males and 257 females; 147 in-service student teachers and 149 pre-service student teachers. The respondents completed a 36-item survey designed by the researcher, which had adequate psychometric properties. The results of the study revealed that internet was the most popular medium for teachers to gain knowledge. In-service student teachers were found to be more knowledgeable than pre-service student teachers. Student teachers’ level of knowledge was unrelated to their age and teaching experience. However their level of knowledge somehow was related to their status. The implications of these findings for inclusion and resources for IE and future research in Malaysia are provided.